Nanostructured ultrathin films of alternating sexithiophenes and electropolymerizable polycarbazole precursor layers investigated by electrochemical surface plasmon resonance (EC-SPR) spectroscopy - Saengrawee Sriwichai (2018)
Nanostructured ultrathin films of linear and dendrimeric cationic sexithiophenes, 6TNL and 6TND, respectively, alternated with anionic polycarbazole precursor, poly(2-(N-carbazolyl) ethyl methacrylate-co-methacrylic acid) or PCEMMA32, were successfully fabricated using the layer-by-layer self-assembly deposition technique. The two electro-optically active oligomers exhibited distinct optical properties and aggregation behavior in solution and films as studied by UV-vis and fluorescence spectroscopy. The stepwise increase of the 6TNL/PCEMMA32 and 6TND/ PCEMMA32 layers was confirmed by UV -vis spectroscopy and in situ surface plasmon resonance (SPR) spectroscopy. The intralayer electrochemical polymerization and cross-linking behavior of the carbazole functionalized PCEMMA32 layers were then investigated using cyclic voltammetry (CV) and electrochemical surface plasmon resonance (EC-SPR) spectroscopy. The increase in current with each cycle confirmed intralayer cross-linking followed by the doping-dedoping process within these films. The two types of films differed with respect to dielectric constant and thickness changes before and after electropolymerization, indicating the influence of the oligothiophene layers. This demonstrated for the first time the preparation of highly ordered organic semiconductors alternated with in situ electropolymerizable layers in ultrathin films. © 2008 American Chemical Society.